Masculine self-presentation and distancing from femininity in gay men: an experimental examination of the role of masculinity threat - Hunt, C. J.; Fasoli, F.; Carnaghi, A.; Cadinu, M. (Psychology of Men and Masculinity, 2016)
There is evidence that discrimination directed toward gay men from some heterosexual men is partially driven by heterosexual men attempting to distance themselves from gay men’s perceived femininity. There is also evidence that many gay men wish they were more masculine than they currently are and will distance themselves from other gay men perceived as being feminine. This persisting stereotype that gay men are insufficiently masculine was theorized to lead gay men to be vulnerable to threats to their masculinity so that they would react to such threats by distancing themselves from feminine-stereotyped gay men and by attempting to present themselves as more masculine. The current study subjected 58 Italian gay men (mean age of 29.10 years, SD = 8.25) to either a threat or an affirmation of their masculinity, and observed reactions to vignettes describing masculine- and feminine-stereotyped gay men. It was hypothesized that those subjected to a threat to their masculinity would report less liking for, less comfort with, and less desire to interact with feminine gay men, while reporting greater similarity to masculine gay men. These hypotheses were partially supported: participants who were threatened in their masculinity reported being more similar to masculine gay men (?² = .09), and showed less interest in interacting with feminine gay men (?2 = .09) than participants whose masculinity was affirmed. These findings suggest that, despite the fact that they are often stereotyped as feminine, gay men may still feel pressure to conform to masculine role norms.